2010
DOI: 10.1113/jphysiol.2010.187484
|View full text |Cite
|
Sign up to set email alerts
|

NaV1.1 channels and epilepsy

Abstract: Voltage-gated sodium channels initiate action potentials in brain neurons, and sodium channel blockers are used in therapy of epilepsy. Mutations in sodium channels are responsible for genetic epilepsy syndromes with a wide range of severity, and the Na V 1.1 channel encoded by the SCN1A gene is the most frequent target of mutations. Complete loss-of-function mutations in Na V 1.1 cause severe myoclonic epilepsy of infancy (SMEI or Dravet's Syndrome), which includes severe, intractable epilepsy and comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
363
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 380 publications
(382 citation statements)
references
References 78 publications
7
363
0
6
Order By: Relevance
“…Another study found that APP mice had a deficit in Nav1.1 expression primarily in a subset of fast-spiking GABAergic interneurons that express parvalbumin (46). Wholecell recordings from the interneurons showed that there were defects in action potential firing (46), similar to studies of mice with SCN1A mutations (44). In both the APP and SCN1A mice, seizures can potentially be explained by disinhibition of principal cells, innervated by interneurons that do not release adequate GABA.…”
Section: Pass the Salt: Mechanisms Of Seizures In Mouse Models Of Admentioning
confidence: 74%
“…Another study found that APP mice had a deficit in Nav1.1 expression primarily in a subset of fast-spiking GABAergic interneurons that express parvalbumin (46). Wholecell recordings from the interneurons showed that there were defects in action potential firing (46), similar to studies of mice with SCN1A mutations (44). In both the APP and SCN1A mice, seizures can potentially be explained by disinhibition of principal cells, innervated by interneurons that do not release adequate GABA.…”
Section: Pass the Salt: Mechanisms Of Seizures In Mouse Models Of Admentioning
confidence: 74%
“…However, most Nav1.1 mutations have their ultimate epileptogenic effects by reducing Nav1.1-mediated whole cell sodium currents in GABAergic neurons, resulting in widespread loss of brain inhibition, an ideal background for the genesis of epileptic seizures (for review: Catterall et al 2010, Ragsdale 2008). …”
Section: Fhm Type 3: Sodium Channels and Migrainementioning
confidence: 99%
“…Epilepsy can also arise as a consequence of spontaneous or inherited gene mutations. Interestingly, the latter includes a vast number of channelopathies, in which recurrent seizures arise from single-point mutations, deletions, duplications, or expansions in genes encoding a component of a voltage-or ligand-gated ion channels, but also many other genes that directly or indirectly control brain development and neuronal function and activity (Catterall et al, 2008(Catterall et al, , 2010Galanopoulou et al, 2012).…”
Section: Epilepsymentioning
confidence: 99%